Nursing of a patient with postoperative pain of appendicitis treated with thumbtack needling combined with auricular acupoint pressing therapy (揿针联合耳穴压丸治疗1例急性阑尾炎患者术后疼痛的护理体会) - LIU Yunchao (刘云超); GUO Lian (郭连); WANG Nannan (王楠楠); WANG Yutao (王玉涛); SUN Lei (孙磊) (Association of Integrative Nursing, 2023)
This paper summarized the nursing management for a patient with postoperative pain of appendicitis. Based on the pain assessment and daily care evaluation, the Traditional Chinese Medicine nursing techniques such as thumbtack needling and auricular acupoint pressing therapy were carried out to relieve the postoperative pain of appendicitis and improve the postoperative rehabilitation and quality of life of the patient. (本文总结1例急性阑尾炎术后疼痛患者的护理体会。在完善疼痛评估和日常护理评估的基础上, 实施中医特色护理技术揿针联合耳穴压丸治疗, 同时完善常规护理措施。揿针联合耳穴压丸治疗能够有效缓解急性阑尾炎术后疼痛, 对促进患者术后康复和改善生活质量具有积极意义。)